MEST Regulates the Stemness of Human Periodontal Ligament Stem Cells. (8th July 2020) - Hasegawa, Daigaku; Hasegawa, Kana; Kaneko, Hiroshi; Yoshida, Shinichiro; Mitarai, Hiromi; Arima, Mai; Tomokiyo, Atsushi; Hamano, Sayuri; Sugii, Hideki; Wada, Naohisa; Kiyoshima, Tamotsu; Maeda, Hidefumi
Abstract : Periodontal ligament (PDL) stem cells (PDLSCs) have been reported as a useful cell source for periodontal tissue regeneration. However, one of the issues is the difficulty of obtaining a sufficient number of PDLSCs for clinical application because very few PDLSCs can be isolated from PDL tissue of donors. Therefore, we aimed to identify a specific factor that converts human PDL cells into stem-like cells. In this study, microarray analysis comparing the gene profiles of human PDLSC lines (2-14 and 2-23) with those of a cell line with a low differentiation potential (2-52) identified the imprinted gene mesoderm-specific transcript (MEST). MEST was expressed in the cytoplasm of 2-23 cells. Knockdown of MEST by siRNA in 2-23 cells inhibited the expression of stem cell markers, such as CD105, CD146, p75NTR, N-cadherin, and NANOG; the proliferative potential; and multidifferentiation capacity for osteoblasts, adipocytes, and chondrocytes. On the other hand, overexpression of MEST in 2-52 cells enhanced the expression of stem cell markers and PDL-related markers and the multidifferentiation capacity. In addition, MEST-overexpressing 2-52 cells exhibited a change in morphology from a spindle shape to a stem cell-like round shape that was similar to 2-14 and 2-23 cell morphologies. These results suggest that MEST plays a critical role in the maintenance of stemness in PDLSCs and converts PDL cells into PDLSC-like cells. Therefore, this study indicates that MEST may be a therapeutic factor for periodontal tissue regeneration by inducing PDLSCs.